Praksis Feminisme Menurut Pandangan KH. Ahmad Dahlan - Mulya, Gani; Mulkhan, Abdul Munir; Sari, Zamah (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2025)
Nowadays, modernization for women from the domestic sphere to the public sphere in various sectors, including education, social, economic and political, is getting an increasing share compared to the time of KH Ahmad Dahlan. Education for women at that time was a luxury.This feminist practice cannot be separated from the role of the founder of Muhamadiyah, namely KH Ahmad Dahlan, who encouraged the establishment of educational movements in the educational and social fields such as: Sopo Tresno and Aisiyah. The researcher wants to describe the practice of feminism according to KH Ahmad Dahlan's views in this article. A description will never be complete, but this article adds to the repertoire of feminist praxis used in everyday life, both individuals and community groups. The aim of the research is to describe matters related to feminist praxis according to the views of Kyai Haji Ahmad Dahlan. The method used in this research is the literature review method, data was collected from relevant library data. The results of this research and discussion are to explain the practice of feminism in everyday life from the time of KH Ahmad Dahlan until today.